Wood color variation in undried and kiln-dried plantation-grown lumber of Vochysia guatemalensis - Aguilar-Tovar, Diana; Moya, Róger; Tenorio, Carolina (Maderas. Ciencia y Tecnología, 2025)
Vochysia guatemalensis has been planted over large tropical areas to obtain lumber products. However, compared with naturally-grown material variations in wood color have been noted. In the current research, trees from two 8-year-old fast-grown plantations were sampled from different climatic conditions in order to identify the causes of color variation. The study evaluated the heartwood presence, grain pattern, distance from pith, height within the tree, and effect of drying schedules. The wood color was measured by CIEL*a*b* systems. Wood color of Vochysia guatemalensis is a combination of different tonalities of lightness (L*), redness (a*), and yellowness (b*), however, the lightness and yellowness components were the dominant tones. The color of heartwood and sapwood were different before and after drying. A negative relationship was found between a* and L*, and a* and b* in the undried state, but no relationship was found between L* and b*. The L* index is only correlated with heartwood presence in undried wood. In dried wood, only a relationship between a* and L* is maintained, while other color parameters were affected by climate, drying schedule and heartwood presence, the L* parameter being the most affected. The dried wood displays a lighter surface than the wood before drying. The variations in the dried wood suggest that it is useful to establish dried lots of lumber according to the drying schedule, source and presence of sapwood and heartwood. La especie Vochysia guatemalensis ha sido plantada sobre largas áreas en regiones tropicales. Así mismo, han sido observadas grandes variaciones del color de su madera. En la investigación fueron muestreadas plantaciones de 8 años de edad en diferentes condiciones de clima con el ﬁn de establecer las causes de variación de la madera. Fueron evaluadas la presencia de duramen, el patrón de aserrío, la distancia de la medula y el programa de secado. El color fue medido por el sistema CIELab. Fue encontrado que la madera de V. guatemalensis presenta una combinación de tonalidades de claros (L*), rojos (a*) y amarrillos (b*), siendo los colores claros y amarrillos los tonos dominantes. El color del duramen y la albura fueron diferentes antes y después del secado. Una negativa correlación entre a* y L*, y a* y b* fue encontrada, pero ninguna correlación fue observada entre L* y b* . El índice L* fue el único parámetro correlacionado con el duramen en madera verde. En la madera seca, solamente se mantuvo la relación a* y L*, mientras que los parámetros del color fueron afectados por el clima, programa de secado y duramen, siendo L* el más afectado. La madera seca presentó una superﬁcie más clara que la madera antes del secado. Las variaciones en madera seca sugieren la conveniencia de establecer lotes de secado de acuerdo al programa de secado aplicado, procedencia y presencia de albura y duramen.